Utilizing a Multi-Proxy to Model Comparison to Constrain the Season and Regionally Heterogeneous Impacts of the Mt. Samalas 1257 Eruption - Wainman, Laura; Marshall, Lauren R.; Schmidt, Anja (Copernicus Publications, 2023)
The Mt. Samalas eruption, thought to have occurred between 1257 and 1258, ranks as one of the most explosive sulfur-rich eruptions of the Common Era. However, the precise year and season of the eruption remains unconstrained with evidence indicating both summer 1257 and early 1258 as potential eruption dates. Widespread surface cooling and hydroclimate perturbations following the eruption have been invoked as contributing to a host of 13th Century social and economic crises, although regional scale variability in the post-eruption climate response remains uncertain. In this study we run ensemble simulations using the UK Earth System Model (UKSEM1) with a range of eruption scenarios and initial conditions in order to compare our simulations with the most complete globally resolved multi-proxy database for the Mt. Samalas eruption to date, incorporating tree-ring, ice core, lake sediment, and historical records. This allows more-precise constraints to be placed on the year and season of the Mt. Samalas eruption as well as an investigation into the regionally heterogeneous post-eruption climate response. Using a multi-proxy to model comparison, we are able to robustly distinguish between July 1257 and January 1258 eruption scenarios where the July 1257 ensemble simulation achieves considerably better agreement with spatially averaged and regionally resolved proxy surface temperature reconstructions. These reconstructions suggest the onset of significant cooling across Asia and Europe in 1258, and thus support the plausibility of previously inferred historical connections. Model-simulated temperature anomalies also point to severe surface cooling across the Southern Hemisphere with as of yet unexplored historical implications for impacted civilizations. A re-evaluation of the use of ice core sulfate deposition records to constrain eruption season and volcanic stratospheric sulfur injection (VSSI) estimates also highlights current limitations in this approach, with our model simulations revealing distinct differences ...